Museums in former residences: castles, palaces and manor houses - Krakowiak, Beata; Latosińska, Jolanta (Turyzm/Tourism, 2009)
The article concerns former residences in Poland and their contemporary use as museums. The authors present the history of Polish residences, the development of museums in castles, palaces and manor houses, their spatial distribution and the relations between the type of building and that of the museum collection.